The 5R Guidelines for a strengths-based approach to co-design with customers experiencing vulnerability. (March 2023) - Russell-Bennett, Rebekah; Kelly, Nick; Letheren, Kate; Chell, Kathleen
This research note addresses a significant gap in the literature in researching marginalised customers who may potentially experience vulnerability: the need to use a strengths-based approach in designing social marketing research. There has been a (positive) trend in recent decades towards greater inclusion of stakeholders in social marketing research, design and evaluation through the adoption of co-design methods. However, a theoretical issue that has not been adequately addressed within social marketing research (with some exceptions) is that it is possible to use co-design methods in such a way that the language and approaches that are employed serve to further disempower these groups through a deficit-based discourse. This research note uses reflexivity to propose a set of guidelines for how to implement a strengths-based approach when co-designing with customers experiencing vulnerability, specifically from a social marketing perspective. A real-world program in the context of empowering mature women to maintain secure housing is used to illustrate the guidelines.